2015
DOI: 10.1016/j.ccell.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The TGF-β Signaling Regulator PMEPA1 Suppresses Prostate Cancer Metastases to Bone

Abstract: SUMMARY Transforming growth factor-β (TGFβ) regulates the expression of genes supporting breast cancer cell in bone but little is known about prostate cancer bone metastases and TGFβ. Our study reveals that the TGFBR1 inhibitor SD208 effectively reduces prostate cancer bone metastases. TGFβ upregulates in prostate cancer cells a set of genes associated with cancer aggressiveness and bone metastases, and the most upregulated gene was PMEPA1. In patients, PMEPA1 expression decreased in metastatic prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
165
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 51 publications
5
165
1
2
Order By: Relevance
“…5 Taken together, TMEPAI is suspected as oncogenic protein. In contrast to above results, Fournier et al 17 recently reported that low of TMEPAI correlates with poor metastasis-free survival and TMEPAI knockdown increases prostate cancer metastases in a mouse model. 17 All the opposite results suggested that TMEPAI has an important function in cancer.…”
Section: Discussioncontrasting
confidence: 65%
“…5 Taken together, TMEPAI is suspected as oncogenic protein. In contrast to above results, Fournier et al 17 recently reported that low of TMEPAI correlates with poor metastasis-free survival and TMEPAI knockdown increases prostate cancer metastases in a mouse model. 17 All the opposite results suggested that TMEPAI has an important function in cancer.…”
Section: Discussioncontrasting
confidence: 65%
“…This hypothesis was convinced by overexpression of TMEPAI in MM cells and resultant MM cell apoptosis. Previous studies showed that TMEPAI does not induce apoptosis of prostate cancer cells but inhibits their proliferation (8,25) and prevents their metastasis (10). This finding is contradicted with its role in some solid cancers, such as lung, ovarian and breast cancers (5,6,11).…”
Section: Discussionmentioning
confidence: 95%
“…4A). A previous study found that TMEPAI has three isoforms, of which the cytosolic form TMEPAIc lacks the TM domain and loses its transcriptional activity (10), suggesting the TM domain is critical for TMEPAI activity. To find out whether the TM domain is critical for TMEPAI-mediated c-Maf ubiquitination and stability, we made a series of short truncates of TMEPAI as shown in Fig.…”
Section: The Transmembrane Domain Is Indispensable For Tmepai-mediatementioning
confidence: 98%
See 1 more Smart Citation
“…In prostate cancer, TGFb forms a growth barrier in response to PTEN deletion (43). Paradoxically, it also promotes the expression of prometastatic genes and the development of bone metastases (44). TGFb is also important in the normal prostate, where cellular interactions between luminal epithelial cells and stromal cells determine the amount of active TGFb, in order to maintain tissue homeostasis (45).…”
Section: Discussionmentioning
confidence: 99%